Case-Based Inpatient Pediatric Dermatology - Hogeling, Marcia (Springer International Publishing : Imprint: Springer, 2016)
Written for pediatric dermatologists, fellows, dermatology residents and medical students rotating in pediatric dermatology, this book covers topics ranging from atopic dermatitis, drug eruptions, neonatal inpatient dermatology, abuse, and skin signs of other systemic diseases. Inpatient Pediatric Dermatology is an emerging subspecialty of Pediatric Dermatology, yet little has been written for the practicing physician treating these young patients in the hospital. Case-based Inpatient Pediatric Dermatology fills that void and uses case-based examples to highlight common and uncommon presentations of dermatologic disease in the hospitalized pediatric patient. Complete with useful color illustrations and photographs, this book is the go-to guide for clinicians treating hospitalized pediatric dermatology patients.